Legal Protection of Copyright and Trademark Rights In the Goods Business - Aditya Restu Hapriyanto; Desi Syamsiah; Putri Maha Dewi (Journal Equity of Law and Governance, 2024)
This research explores various aspects of legal protection for copyright and trademark rights in the goods business, as well as efforts to strengthen this protection. This study aims to answer several key questions, including the effectiveness of existing legal frameworks in protecting copyright and trademarks, as well as the challenges faced in enforcing these rights in the global marketplace. This research specifically identifies gaps in regulation and problems such as inconsistent law enforcement, inadequate protection of new innovations, and difficulties in effectively addressing rights violations. By detailing these issues, this study aims to provide strategic recommendations that can address deficiencies in current legal protection and increase support for rights owners in the goods industry. Effective legal protection in these areas supports innovation and creativity, fosters consumer trust, and contributes to economic growth. However, the enforcement of these rights faces challenges, especially with the rise of digital platforms and global markets, which can complicate both infringement and enforcement processes.